Mathematical Problem Solving Ability of SMP 1 Kelekar Students Analized Based on Student Learning Motivation - Fajri, Hardian Mei; Misdalina, Misdalina; Kesumawati, Nila (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This study aims to describe how the students 'mathematical problem solving abilities in SMP Negeri 1 Kelekar were reviewed from the students' learning motivation on the material of the flat side of the cubes and blocks.  The method used in this research is descriptive quantitative.  The subjects of this study were 24 students of class IX1 SMP Negeri 1 Kelekar.  Data collection techniques in this study were a test of mathematical problem solving abilities and a questionnaire (questionnaire) student learning motivation.  The data analysis technique used descriptive statistics.  The results of the data analysis of this study indicate that: (1) students with a high learning motivation category obtained an average score of mathematical problem solving abilities, namely 70.00 in the moderate category;  (2) students with the moderate learning motivation category obtained an average score of mathematical problem solving abilities, namely 60.66 in the moderate category;  (3) Students with low learning motivation category obtained an average score of mathematical problem solving abilities, namely 41.00 in the low category.Penelitian ini bertujuan untuk mendeskripsikan bagaimana kemampuan pemecahan masalah matematis aiswa SMP Negeri 1 Kelekar ditinjau dari motivasi belajar siswa pada materi bangun ruang sisi datar kubus dan balok. Metode yang digunakan dalam penelitian ini yaitu deskriptif kuantitatif. Subjek dari penelitian ini yaitu siswa kelas IX1 SMP Negeri 1 Kelekar yang berjumlah 24 siswa. Teknik pengumpulan data dalam penelitian ini adalah tes kemampuan pemecahan masalah matematis dan kuesioner (angket) motivasi belajar siswa. Teknik analisis data menggunakan statistik deskriptif. Hasil analisis data penelitian ini menunjukan bahwa: (1) siswa dengan kategori motivasi belajar tinggi memperoleh nilai rata-rata kemampuan pemecahan masalah matematis yaitu 70,00 kategori sedang; (2) siswa dengan kategori motivasi belajar sedang memperoleh nilai rata-rata kemampuan pemecahan masalah matematis yaitu 60,66 kategori sedang; (3) siswa dengan kategori motivasi belajar rendah memperoleh nilai rata-rata kemampuan pemecahan masalah matematis yaitu 41,00 kategori rendah.